The influence of breed, age, gender, training level and ambient temperature on forelimb and back temperature in racehorses. (27th June 2016) - Soroko, Maria; Howell, Kevin; Dudek, Krzysztof; Henklewski, Radomir; Zielińska, Paulina
Abstract: A previous thermographic study of racehorses identified 13 regions of interest (ROIs) for monitoring the impact of training. However, that investigation did not consider the influence of breed, age, gender or training intensity level on the temperature of ROIs. The present study adopted a multivariate analysis approach to determine whether the aforementioned factors, along with ambient temperature, significantly influenced ROI temperature in the key body regions. Thermography measurements were obtained from 53 racehorses of three breeds. Horses were in regular training for over 10 months, having 13 thermographic examinations in each racing season. Backward stepwise multiple linear regression indicated that ambient temperature and breed contributed significantly to the model for predicting ROI temperature at all 13 ROIs. Training intensity level contributed significantly to the model only at the thoracic vertebrae, the left third metacarpal bone and left fetlock joint. Neither gender nor age contributed to the model significantly at any ROI. Our data suggest that ambient temperature, breed and training level affect racehorse body surface temperature in some areas of the distal parts of the forelimbs and the back. This contributes to a better understanding of the normal range of thermographic findings in racehorses undergoing intensive training.